2009
DOI: 10.1111/j.1365-2613.2008.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of lethal inhalational infection with Francisella tularensis (tularaemia) in the common marmoset (Callithrix jacchus)

Abstract: Susceptibility and lethality studies of inhalational tularaemia were undertaken using the common marmoset (Callithrix jacchus) to determine its suitability as a non-human primate model. Pairs of marmosets were exposed to varying challenge doses of Francisella tularensis by the airborne route and monitored for up to 14 days postchallenge (p.c.). Lethal infection was achieved following a retained dose of less than 10 bacterial colony-forming units (CFU). However, precise LD(50) determination was not possible. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…While mice have largely served as the primary animal model for attenuation and protection studies, they are far more sensitive to type B strains than humans, and thus are not an ideal model for tularemia. Recent advances have been made in modeling human tularemia infection in rabbits, rats, and monkeys [11, 5156]. One recent non-human primate study demonstrated that Schu S4 mutants of the dsbB and pdpB genes were shown to be attenuated in rhesus macaque monkeys and partially protective against an i.n.…”
Section: Discussionmentioning
confidence: 99%
“…While mice have largely served as the primary animal model for attenuation and protection studies, they are far more sensitive to type B strains than humans, and thus are not an ideal model for tularemia. Recent advances have been made in modeling human tularemia infection in rabbits, rats, and monkeys [11, 5156]. One recent non-human primate study demonstrated that Schu S4 mutants of the dsbB and pdpB genes were shown to be attenuated in rhesus macaque monkeys and partially protective against an i.n.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the effects of IRS on bacterial growth were most clearly observed in the infected liver and spleen. The liver is a major site of F. tularensis colonization and replication (9), and pneumonic tularemia is associated with hepatocellular damage in multiple experimental animal models, including the F344 rat (8,32,42,45). Although the level of damage falls short of liver failure and may be reversible, such damage may nevertheless compromise the liver's ability to perform essential metabolic functions and to utilize its many innate immune mechanisms to control systemic bacterial growth (22,25).…”
Section: Vol 79 2011mentioning
confidence: 99%
“…Some information is also provided by experimental infections [40][41][42][43]. Primates, lagomorphs, and rodents are very susceptible and sensitive to the disease.…”
Section: Animalsmentioning
confidence: 99%